Analysis of Suicide Cases from Ankara Province: A 3-year Emergency Medical Services Experience - Usul, Eren; Şan, İshak and Korkut, Semih and Kayıpmaz, Selvi and Bekgöz, Burak (Acta Biomedica Atenei Parmensis, 2022)
Aim: While the term "completed suicide" refers to suicides that have resulted in death,"suicide attempts" refers to all attempts that do not result in death.Analyzing EMS cases is a reliable method of obtaining data on suicide attempts and completed suicides. We aimed to determine the relationship between the occurrence of cases on weekdays, weekends, public holidays or long holidays and case characteristics. Methodology: We evaluated EMS data of Ankara Province on completed suicide and suicide attempts including the date range 01.01.2017- 31.12.2019. We evaluated the data in terms of age, gender, mortality at the scene, and suicide method. In addition, we evaluated the data according to the hour, day, month, season, and year of the cases. We classified the suicide cases according to their occurrence on weekdays, weekends, public holidays or long holidays.Results: During the 3-year period included in the study, Ankara EMS assigned ambulances to a total of 940,546 cases. Of these cases, 8231 (0.875%) were suicide attempts and completed suicides. Suicide attempts were most frequent in males, in the 20-24 age group, in summer, in July, on Sundays, and between the hours 18:00 and 24:00. The most common method in suicide attempts was self-poisoning by drugs. Completed suicides were most frequent in males, in the 30-34 age group, in spring, in May, on Mondays and Tuesdays, and between the hours 18:00 and 24:00. Conclusion: We evaluated different characteristics of suicide cases of EMS. In Turkey, there are few studies in the EMS field on this issue. Therefore, we believe that this study will contribute to the epidemiological evaluation of suicides. We hope that results of this study will help to prevent both suicides and suicide attempts.